2020
DOI: 10.1177/0886260520966671
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Help-seeking Strategies in Response to Intimate Partner Violence: A Latent Class Analysis

Abstract: Women engage in multiple strategies to cope with the impact of intimate partner violence (IPV). Prior research has focused predominantly on women’s service utilization and help seeking as individual acts, yet it is likely that women engage in distinct patterns of multiple help-seeking strategies to achieve safety. As such, the current article examines patterns of service-related help-seeking strategies survivors employ. This article also investigates demographic factors, relationship characteristics, and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
2
19
2
Order By: Relevance
“…Survivors’ decisions regarding help-seeking are influenced by a number of variables, including but not limited to their children (Davies and Lyon, 2014; Duterte et al, 2008; Palmer et al, 2016), their personal economic stability (Davies et al, 2008), their relationship with their partner (Duterte et al, 2008; Felson et al, 2002), a desire to protect their partner (Davies et al, 2008; Davies and Lyon, 2014; Felson et al, 2002; Fugate et al, 2005; Reaves, 2017), the type of violence they have experienced (Ben-Porat, 2020; Davies and Lyon, 2014; Duterte et al, 2008; Jordan, 2004), minimization of the abuse (Davies et al, 2008; Fugate et al, 2005; Reaves, 2017), fear of retaliation (Felson et al, 2002; Fugate et al, 2005; Reaves, 2017), accessibility and availability of resources, and their experience using other resources (Davies and Lyon, 2014). Recent research in the United States examining patterns of help-seeking among survivors has found that there is a group of survivors who avoid legal system interventions (Cheng et al, 2020; Hanson et al, 2019), enhancing the need for understanding decision-making among survivors who choose not to engage with the legal system.…”
Section: Help-seeking Among Ipv Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survivors’ decisions regarding help-seeking are influenced by a number of variables, including but not limited to their children (Davies and Lyon, 2014; Duterte et al, 2008; Palmer et al, 2016), their personal economic stability (Davies et al, 2008), their relationship with their partner (Duterte et al, 2008; Felson et al, 2002), a desire to protect their partner (Davies et al, 2008; Davies and Lyon, 2014; Felson et al, 2002; Fugate et al, 2005; Reaves, 2017), the type of violence they have experienced (Ben-Porat, 2020; Davies and Lyon, 2014; Duterte et al, 2008; Jordan, 2004), minimization of the abuse (Davies et al, 2008; Fugate et al, 2005; Reaves, 2017), fear of retaliation (Felson et al, 2002; Fugate et al, 2005; Reaves, 2017), accessibility and availability of resources, and their experience using other resources (Davies and Lyon, 2014). Recent research in the United States examining patterns of help-seeking among survivors has found that there is a group of survivors who avoid legal system interventions (Cheng et al, 2020; Hanson et al, 2019), enhancing the need for understanding decision-making among survivors who choose not to engage with the legal system.…”
Section: Help-seeking Among Ipv Survivorsmentioning
confidence: 99%
“…Additionally, data were collected at a single point in time, usually early in a participant’s shelter stay. Some survivors specifically choose not to use the legal system but are amenable to using social services (Cheng et al, 2020; Hanson et al, 2019). Future research should collect interview or focus group data to examine in more depth why survivors opt not to seek POs and/or use the legal system as a resource.…”
Section: Limitationsmentioning
confidence: 99%
“…Indeed, research indicates that survivors access social services differentially. While women who experience high levels of IPV are generally more likely to access formal social services, some survivors may only seek informal assistance (Cheng et al, 2020; Hanson et al, 2019). Survivors of color factor in for racism and discriminatory practices as they determine when and how to seek help (St.…”
Section: Risk-informed Interventionsmentioning
confidence: 99%
“…Nearly half of intimate partner violence (IPV) survivors experience their rst abusive relationship at college age (18)(19)(20)(21)(22)(23)(24). In research studies, between 10-65% of US college students report experiencing violence from an intimate/dating partner or ex-partner (Barrick et al, 2013;Shorey et al, 2011), with the wide range likely attributable to varying operational de nitions, populations, and samples.…”
Section: Introductionmentioning
confidence: 99%